POLLEN AND PROTEIN RESIDUE ANALYSIS OF ARTIFACTS FROM SITE 24HL1215 IN THE BEAR PAW MOUNTAINS, MONTANA - Cummings, Linda Scott (PaleoResearch Institute); Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
Five pieces of groundstone or probable groundstone were submitted for pollen/starch and protein residue analysis to determine what animals and plants might have bee~ processed using these tools. Site 24HL1215 is situated on a low and narrow terrace overlooking the East Fork of Beaver Creek in Hill County, Montana.